Characterization of Glycopeptide-Resistant Enterococci from a Swiss Hospital - Liassine, Nadia (American Society for Microbiology, 1998)
Between August 1994 and September 1996, 28 glycopeptide-resistant enterococci (GRE) were isolated from 8 infected patients and 11 intestinal carriers hospitalized at the University Hospital of Geneva. Identification to the species was made by both phenotypic (API 20 STREP and Rapid ID 32 STREP systems, and Vitek Gram Positive Identification Card) and genotypic methods using a multiplex PCR assay developed also for the determination of the genotype of glycopeptide resistance (vanA, vanB, vanC1, and vanC2-C3 genes). Fifteen isolates were identified as Enterococcus faecium, 8 as E. gallinarum, 4 as E. faecalis, and 1 as E. hirae. All of the phenotypic identification methods failed to differentiate some isolates of E. gallinarum from E. faecium, or vice versa. Both vanA (n = 18) and vanB (n = 4) glycopeptide resistance genotypes were found. For the first time, the vanB determinant was found in two isolates of E. gallinarum. Two patients were colonized by two different species containing the vanA gene and one by two different species containing the vanB gene. All vanA isolates were highly resistant to both vancomycin and teicoplanin except for three isolates which were susceptible to teicoplanin. Molecular typing by pulsed-field gel electrophoresis showed identical or similar patterns among E. faecium isolates with the vanA gene in five patients for whom the epidemiological link could not be always elucidated. This study emphasizes the necessity of utilizing both phenotypic and genotypic methods to characterize GRE.